Technological Characteristics of Melon Fruits Intended for Processing - Sultanov Jetkerbay Davletbayevich; Umidov Shavkat Ergashevich (Journal of Medical Genetics and Clinical Biology, 2024)
In the article, the results of the research conducted in order to study the technological characteristics of the fruits of melon varieties intended for processing are presented with a deep scientific analysis.